2018
DOI: 10.17159/2410-972x/2018/v28n2a17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals and radionuclides in dust fallout in the West Rand mining area of South Africa

Abstract: Windblown dust can contain radioactive materials from mining. These radionuclides when inhaled in dust produce ionizing radiation which damages the cells and tissues in the body. The aim of this study was to assess dust fallout radionuclides in the West Rand mining area of South Africa. Dust fallout monitoring was done using the method (ASTM) D-1739 of 1998 employing multi-directional buckets. Results show that all 9 locations investigated in the different seasons recorded dust fallout rates within stipulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To examine the potential health impacts that could be posed by the heavy metals, enrichment factors were calculated. According to Dudu et al [ 41 ], the enrichment factor (EF) method is one way of quantifying the anthropogenic pollution of a given site. The assumption made in calculating EF is that the ratio is 1 for elements not above crustal average.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the potential health impacts that could be posed by the heavy metals, enrichment factors were calculated. According to Dudu et al [ 41 ], the enrichment factor (EF) method is one way of quantifying the anthropogenic pollution of a given site. The assumption made in calculating EF is that the ratio is 1 for elements not above crustal average.…”
Section: Resultsmentioning
confidence: 99%
“…South Africa, which has one of the most diverse and comprehensive farming systems in Africa, is known for its mining and industrial activities, resulting in radioactive waste littered in farmlands and communities ( 7 ) . South Africa is a water-scarce country, having about 12% of the country’s land suitable for growing rain-fed crops with 3% considered fertile, and about 1.3 million ha of land under irrigation, which represents 60% of the total water use per sector, according to Baleta and Pegram ( 8 ) , contributing significantly to the food chain, which serves as direct exposure source through ingestion of food crop.…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter refers to a mixture of atmospheric solid and liquid particles that vary in number, morphology (size, shape, and surface features), chemical composition, density, solubility, and origin. Particulate matter also represents suspended dust that is settleable or can be deposited at a particular site in the atmosphere and referred to then as dust fallout (Dudu et al, 2018;Liebenberg-Enslin et al, 2020;Pope & Dockery, 2006). Dust fallout or dust in general is constantly emitted into the ambient air from a variety of activities and sources that can be natural or anthropogenic.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of pollutants and/or microbial diversity has been associated with dust and/or dust fallout particles (Al-Barakah et al, 2014;Gonzalez-Martin et al, 2014). Chemical pollutants that are of concern that can be absorbed or incorporated into dust of a given location (with respect to their origin) include a variety of trace metals (i.e., arsenic, chromium, nickel, lead, copper, cadmium, and mercury) (Kgabi, 2010;Kgabi et al, 2012;Lanzerstorfer, 2021;Popoola et al, 2012), radionuclides mostly linked to mining sites and its associated processes (i.e., radium and thorium) (Dudu et al, 2018) as well as other contaminants. Previous studies have shown that dust and/or dust fallout particles have been correlated with viable microorganisms or cells (i.e., non-pathogenic, and pathogenic bacteria, viruses, and fungi) which can emanate from humans and plants in addition to other sources such as pets (Babu et al, 2017;Chen et al, 2023;Malli Mohan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%